Efficacy and safety of lumasiran for infants and young children with primary hyperoxaluria type 1: 30-month analysis of the phase 3 ILLUMINATE-B trial - Frishberg, Yaacov; Hayes, Wesley; Shasha-Lavsky, Hadas; Sas, David J.; Michael, Mini; Sellier-Leclerc, Anne-Laure; Hogan, Julien; Willey, Richard; Gansner, John M.; Magen, Daniella (Frontiers in Pediatrics, 2024)
Background: Primary hyperoxaluria type 1 (PH1) is a genetic disorder resulting in overproduction of hepatic oxalate, potentially leading to recurrent kidney stones, nephrocalcinosis, chronic kidney disease, and kidney failure. Lumasiran, the first RNA interference therapeutic approved for infants and young children, is a liver-directed treatment that reduces hepatic oxalate production. Lumasiran demonstrated sustained efficacy with an acceptable safety profile over 12 months in infants and young children (age <6 years) with PH1 in ILLUMINATE-B (clinicaltrials.gov: NCT03905694), an ongoing, Phase 3, multinational, open-label, single-arm study. Methods: Here, we report interim efficacy and safety findings from ILLUMINATE-B following 30 months of lumasiran treatment. Eligible patients had an estimated glomerular filtration rate (eGFR) >45 mL/min/1.73m2 if ≥12 months old or normal serum creatinine if <12 months old, and a urinary oxalate to creatinine ratio (UOx:Cr) greater than the upper limit of normal. All 18 patients enrolled in ILLUMINATE-B completed the 6-month primary analysis period, entered an extension period of up to 54 months, and continue to participate in the study. Results: At Month 30, mean percent change from baseline in spot UOx:Cr was −76%, and mean percent change in plasma oxalate was −42%. eGFR remained stable through Month 30. In 14 patients (86%) with nephrocalcinosis at baseline, nephrocalcinosis grade improved at Month 24 in 12; no patient worsened. In the 4 patients without baseline nephrocalcinosis, nephrocalcinosis was absent at Month 24. Kidney stone event rates were ≤0.25 per person-year through Month 30. Mild, transient injection site reactions were the most common lumasiran-related adverse events (17% of patients). Conclusion: In infants and young children with PH1, long-term lumasiran treatment resulted in sustained reductions in urinary and plasma oxalate that were sustained for 30 months, with an acceptable safety profile. Kidney function remained stable, low kidney stone event rates were observed through Month 30, and nephrocalcinosis grade improvements were observed through Month 24.